2017
DOI: 10.1039/c6ra28110a
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties of betaxanthins: miraxanthin V – insight into the excited-state deactivation mechanism from experiment and computations

Abstract: Fast radiationless S1 → S0 transition in photo-excited betaxanthins is due to conical intersection seam between S1 and S0 surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 62 publications
0
18
0
18
Order By: Relevance
“…In betalains it has been demonstrated that this value is proportional to the viscosity of the solvent used (Table 1). Thus, the analysis in water and methanol gives lower values than in ethylene glycol [37,[39][40][41]. This response has also been shown for betaxanthin molecules present in gelificating media, where fluorescence intensity increases with the time course of the process [42].…”
Section: Photophysicsmentioning
confidence: 61%
See 3 more Smart Citations
“…In betalains it has been demonstrated that this value is proportional to the viscosity of the solvent used (Table 1). Thus, the analysis in water and methanol gives lower values than in ethylene glycol [37,[39][40][41]. This response has also been shown for betaxanthin molecules present in gelificating media, where fluorescence intensity increases with the time course of the process [42].…”
Section: Photophysicsmentioning
confidence: 61%
“…Betanin 0.0007 0.0013 0.0047 [37] Indicaxanthin 0.0053 0.0081 0.033 [39] Miraxanthin V 0.003 0.0047 0.015 [41] Vulgaxanthin I 0.0073 0.011 0.039 [40] Miraxanthin I 0.0084 -- [34] show that an increase in the viscosity of the medium makes the convection of the acquired energy difficult, favoring the path of the fluorescence. The presence of aromatic rings linked to the electron resonance system characteristic of betalamic acid implies a marked decrease in the fluorescence intensity.…”
Section: Photophysicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Embora a largura do pulso a meia altura seja de ca.6 ps, observa-se no intervalo < 1 ps a mudança do máximo desta transição, bem como da emissão estimulada (SE, banda negativa próxima a 620 nm), para comprimentos de onda mais longos, fato que pode estar relacionado a solvatação da espécie localmente excitada.As duas bandas negativas, uma com máximo em 578 nm e outra em 634 nm, referem-se à recomposição do estado fundamental (branqueamento, bleaching) e à emissão estimulada (SE), respectivamente. Este perfil observado é similar aos dados da literatura para as betalaínas Bn, BtP, vulgaxantina-I e miraxantina-V 36,37,39,40. Todos os processos observados tem tempo de vida próximo a 14 ps, valor calculado através do ajuste não linear da variação da absorção em função do tempo com função monoexponencial (anexo 7.7).…”
unclassified